A new perspective on the radio active zone at the Galactic center – feedback from nuclear activities. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Zhao, J.-H.; Morris, M. R.; Goss, W. M.
Abstract: Based on our deep image of Sgr A using broadband data observed with the VLA† at 6 cm, we present a new perspective of the radio bright zone at the Galactic center. We further show the radio detection of the X-ray Cannonball, a candidate neutron star associated with the Galactic center SNR Sgr A East. The radio image is compared with the Chandra X-ray image to show the detailed structure of the radio counterparts of the bipolar X-ray lobes. The bipolar lobes are likely produced by the winds from the activities within Sgr A West, which could be collimated by the inertia of gas in the CND, or by the momentum driving of Sgr A*; and the poloidal magnetic fields likely play an important role in the collimation. The less-collimated SE lobe, in comparison to the NW one, is perhaps due to the fact that the Sgr A East SN might have locally reconfigured the magnetic field toward negative galactic latitudes. In agreement with the X-ray observations, the time-scale of ∼1 × 10 4 yr estimated for the outermost radio ring appears to be comparable to the inferred age of the Sgr A East SNR.